CONSUMPTION BEHAVIOR OF ISLAMIC ECONOMIC PERSPECTIVE DURING THE COVID-19 PANDEMIC - Alma Alma; Muhammad Wahyuddin Abdullah; Sirajuddin (Profetika: Jurnal Studi Islam, 2023)
The purpose of this study is to determine the impact and consumptive behavior of students from an Islamic economic perspective. The research methodology used is a qualitative descriptive field research and research locations on students at the Faculty of Economics and Islamic Business. The criteria used by researchers are students who like to shop online or directly to sellers. Students who have an above average economy or students who have their own income. And students whose lives follow the trend. The results of this study indicate that the consumptive behavior of the students of the Faculty of Economics and Islamic Business during the pandemic is still relatively active in the form of impulse buying, waste, and seeking pleasure. Consumptive behavior from an Islamic economic perspective is a bad deed,